Public attitudes toward the research use and storage of residual dried blood spots from newborn screening in China - Xiaoshan Yin; Peiyao Wang; Yaru Liu; Kaixing Le; Ziyan Cen; Qimin He; Benqing Wu; Xinwen Huang (BMC Medical Ethics)
Abstract Purpose To examine public attitudes in China toward storing and using residual dried blood spots (DBS) from newborn screening (NBS). Methods A self-designed questionnaire was administered to expectant or current parents using a non-probability sampling approach that combined convenience and snowball sampling. The survey contained questions about demographics, awareness of NBS, willingness to use DBS for research with or without parental permission, willingness to store, and preferred storage duration. Multiple logistic regression was used to identify factors associated with NBS awareness and support for DBS storage. Results Among 1,490 respondents, 42.5% were aware of NBS. Awareness was higher among those with a master’s degree (vs. junior high school, OR = 4.09, 95% CI: 2.07–8.07), income above 200,000 RMB (vs. less than 50,000, OR = 2.52, 95% CI: 1.75–3.63), and two children (vs. none, OR = 2.28, 95% CI: 1.48–3.52). Support for DBS use in research was 77.5% with parental permission and 52.0% without. Parents very willing to use DBS for research were more likely to support storage with permission (aOR = 30.11, 95% CI: 12.19–74.35) and without (aOR = 5.61, 95% CI: 2.09–15.07). Preference for indefinite storage was associated with higher support for storage than preference for a set period (aOR = 5.11, 95% CI: 3.43–7.63). Conclusion In our study, less than half were aware of NBS, yet most supported DBS use for research with consent. NBS awareness, positive research attitudes, and preference for long-term storage were linked to greater willingness to store DBS. Interventions should prioritize standardized consent procedures, prenatal education, and flexible storage options that accommodate diverse preferences.